Analisis Struktural Naskah Drama Laa Taghdob Karya Azis Moa Sebagai Bahan Ajar di Kelas XI - Amelia Nurfitri Annisa; Evi Fatmalasari; Silfa Milatul Istiqomah; Adita Widara Putra (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
A drama text or script is a story performed on stage that tells the lives of the characters with such a plot. Drama as a literary genre has two dimensions, namely the literary dimension and the performing arts dimension. As a literary dimension, drama is focused on a script written by the author in dialogue form so that it can be read, enjoyed and understood by the reader. Meanwhile, as a dimension of performing arts, drama is focused on performances on stage. Drama has its own special features, compared to other literary genres. Structural studies in literary research are an approach that emphasizes the idea that a literary work is something that stands alone from other elements. Intrinsic elements do not only consist of theme, events, characters, plot, setting, message and point of view, but in a drama script you will also study the title, theme, wawancang and kramagung, acts and scenes, characterization and character, conflict, plot. , setting, dialogue techniques, drama types.